A Bipolar and Self‐Polymerized Phthalocyanine Complex for Fast and Tunable Energy Storage in Dual‐Ion Batteries. (24th June 2019) - Wang, Heng‐guo; Wang, Haidong; Si, Zhenjun; Li, Qiang; Wu, Qiong; Shao, Qi; Wu, Lanlan; Liu, Yu; Wang, Yinghui; Song, Shuyan; Zhang, Hongjie
Abstract: Bipolar redox organics have attracted interest as electrode materials for energy storage owing to their flexibility, sustainability and environmental friendliness. However, an understanding of their application in all‐organic batteries, let alone dual‐ion batteries (DIBs), is in its infancy. Herein, we propose a strategy to screen a variety of phthalocyanine‐based bipolar organics. The self‐polymerizable bipolar Cu tetraaminephthalocyanine (CuTAPc) shows multifunctional applications in various energy storage systems, including lithium‐based DIBs using CuTAPc as the cathode material, graphite‐based DIBs using CuTAPc as the anode material and symmetric DIBs using CuTAPc as both the cathode and anode materials. Notably, in lithium‐based DIBs, the use of CuTAPc as the cathode material results in a high discharge capacity of 236 mAh g −1 at 50 mA g −1 and a high reversible capacity of 74.3 mAh g −1 after 4000 cycles at 4 A g −1 . Most importantly, a high energy density of 239 Wh kg −1 and power density of 11.5 kW kg −1 can be obtained in all‐organic symmetric DIBs. Abstract : Schnell und abstimmbar : Ein bipolarer und selbstpolymerisierbarer Phthalocyanin‐Komplex wird als polaritätsschaltbares Elektrodenmaterial für Lithium‐ und Graphit‐basierte Dual‐Ionen‐Batterien genutzt, einschließlich organischen symmetrischen Dual‐Ionen‐Batterien. Dieser Ansatz kann die Lücke zwischen organischen Batterien und Dual‐Ionen‐Batterien schließen.